# Solve for y 19-(2y+3)=(2y+3)+y

19-(2y+3)=(2y+3)+y
Since y is on the right side of the equation, switch the sides so it is on the left side of the equation.
(2y+3)+y=19-(2y+3)
3y+3=19-(2y+3)
Simplify 19-(2y+3).
Simplify each term.
Apply the distributive property.
3y+3=19-(2y)-1⋅3
Multiply 2 by -1.
3y+3=19-2y-1⋅3
Multiply -1 by 3.
3y+3=19-2y-3
3y+3=19-2y-3
Subtract 3 from 19.
3y+3=-2y+16
3y+3=-2y+16
Move all terms containing y to the left side of the equation.
Add 2y to both sides of the equation.
3y+3+2y=16
5y+3=16
5y+3=16
Move all terms not containing y to the right side of the equation.
Subtract 3 from both sides of the equation.
5y=16-3
Subtract 3 from 16.
5y=13
5y=13
Divide each term by 5 and simplify.
Divide each term in 5y=13 by 5.
5y5=135
Cancel the common factor of 5.
Cancel the common factor.
5y5=135
Divide y by 1.
y=135
y=135
y=135
The result can be shown in multiple forms.
Exact Form:
y=135
Decimal Form:
y=2.6
Mixed Number Form:
y=235
Solve for y 19-(2y+3)=(2y+3)+y

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top